Power cable simulation of failure through temperature monitoring of optical fibres with a state-of-the-art distributed sensing instrument - Ioannou, Andreas; Metaxas, Andreas; Argyrou, Maria C.; Kouzoupou, Charalambos; Kalli, Kyriacos; Chatzis, Sotirios P.; Panaretou, Georgios; Marchesini, Pierpaolo; Mondanos, Michael; Karaulanov, Rumen; Agathocleous, Michalis; Dionysiou, Antreas; et al. (My University, 2023)
In this work we utilize multimode optical fibers for the detection of simulated errors or failures in underground power cables. It is known that in cases of failure the underground transmission cables overheat locally, they become a hot-spot, and it is extremely difficult to detect and locate the problem. The proposed methodology is as follows, having an underground electric cable we simulate various temperature profiles whilst the optical fiber was placed in selected distances away from our simulated fault to examine the detection performance of our fiber. In this way we aim to stabilize the operation of the underground cable damage detection system that is placed by the Electricity Authority of Cyprus. The EAC has certain locations where the existing single-mode optical fibres are collocated with the underground power cables, although relative spacing may not be constant. Our data will give an indication of how important is uniform spacing between power and optical cables. We examine if any change in the temperature of the power cable is also reflected in the optical fibre cable. The real-time and continuous monitoring of the temperature of the optical cables through the distributed sensing systems may help identifying abnormal cable behaviour (hot spots) and possible future network failures in the power network.
Keywords: Distributed sensing; optical fibers